Influence of temperature and heating rates on calcination of waste cockle shells to calcium oxides - Nur Atifah, Ahmad Kamil Saraidin (2014)
Cockle shells or Anadara granosa has been touted as an alternative for the calcium carbonate sources instead of using the limestone. Mining large quantities of rocks can contribute to the environmental damage and engage with the high cost for environmental compliance. Li et al. (2009) also proved that seashells to have higher composition of calcium oxides compared to the limestones. In this research, the shells of Malaysian blood cockle, Anadara granosa, were used as the starting material. The present study was done to evaluate the influence of operating conditions on the minerals of Anadara granosa shells by heat treatment at various temperatures and heating rates, and to subsequently use the resulting material for the formation of calcium oxide. CaO associated with carbonaceous material has been of recent interest in applications such as transesterification catalysts and sorbents for sulphur dioxide. The utilisation of the economic resources of waste bio-minerals from blood cockle shells is expected to promote the commercial application of the resulting calcium oxides. Calcination of cockle shells was analysed with TGA with different range of temperature (700, 750, 800, 850 and 900oC) and heating rates at 10oC/min and 20oC/min. Overall, the better performance is shown at the calcination temperature of 800oC for 39 minutes and heating rate of 20oC/min under N2 gas flow of 40mL/min. Then, the characterization of the cockle shells are done by the FTIR spectrophotometer which is performed in a range of 4000cm-1 to 400 cm-1 with a resolution of 2 cm-1 and averaging of 62 scans. As result, the FTIR analysis showed that the waste cockle shell from the seashore gave the peak of 1472.99cm-1